Dictation, a production exercise written par excellence - OUAL, Amel; ABADI , Dalila (Journal of Human Sciences, 2022)
French spelling has not stopped evolving over time, it represents the graphic and semantic identity of the language, it has undergone several modifications and changes: it is "the new spelling". His knowledge is essential in learning each language. Spelling education aims to give the learner all the necessary skills he needs to know his language to speak and write correctly. However, our students and especially those of the 1st year average find major difficulties in writing. In this article, we will explain that writing flawless text always remains an obstacle for learners and there is no better than dictation to fill this gap. Dictation, this written production exercise often overlooked by current French-language programs, always remains a means of linguistic remediation.